Microcambeva ribeirae sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new sarcoglanidine catfish from the Rio Ribeira do Iguape basin, southeastern Brazil - Costa, Wilson J.e.m.; Lima, Sérgio M.q.; Bizerril, Roberto S.f. (Zootaxa, 2004)
A second species of Microcambeva, M. ribeirae, is described from the Rio Ribeira do Iguape basin, S o Paulo, southeastern Brazil, which constitutes the southernmost record for sarcoglanidine catfishes. It is distinguished from M. barbata by a series of morphological features, including nasal barbel extent, position of the eye, first pectoral-fin ray extent, position of the anal fin, position of the posterior pore of the supraorbital canal, frontal shape, cranial fontanel extent, lateral process of the sphenotic, absence of the anterior ossification of palatine, and size of the posterior process of the palatine and supraorbital bone.